Journey of oocyte from metaphase‐I to metaphase‐II stage in mammals. Issue 8 (6th March 2018) - Sharma, Alka; Tiwari, Meenakshi; Gupta, Anumegha; Pandey, Ashutosh N.; Yadav, Pramod K.; Chaube, Shail K.
Abstract : In mammals, journey from metaphase‐I (M‐I) to metaphase‐II (M‐II) is important since oocyte extrude first polar body (PB‐I) and gets converted into haploid gamete. The molecular and cellular changes associated with meiotic cell cycle progression from M‐I to M‐II stage and extrusion of PB‐I remain ill understood. Several factors drive oocyte meiosis from M‐I to M‐II stage. The mitogen‐activated protein kinase3/1 (MAPK3/1), signal molecules and Rho family GTPases act through various pathways to drive cell cycle progression from M‐I to M‐II stage. The down regulation of MOS/MEK/MAPK3/1 pathway results in the activation of anaphase‐promoting complex/cyclosome (APC/C). The active APC/C destabilizes maturation promoting factor (MPF) and induces meiotic resumption. Several signal molecules such as, c‐Jun N‐terminal kinase (JNK2), SENP3, mitotic kinesin‐like protein 2 (MKlp2), regulator of G‐protein signaling (RGS2), Epsin2, polo‐like kinase 1 (Plk1) are directly or indirectly involved in chromosomal segregation. Rho family GTPase is another enzyme that along with cell division cycle (Cdc42) to form actomyosin contractile ring required for chromosomal segregation. In the presence of origin recognition complex (ORC4), eccentrically localized haploid set of chromosomes trigger cortex differentiation and determine the division site for polar body formation. The actomyosin contractile activity at the site of division plane helps to form cytokinetic furrow that results in the formation and extrusion of PB‐I. Indeed, oocyte journey from M‐I to M‐II stage is coordinated by several factors and pathways that enable oocyte to extrude PB‐I. Quality of oocyte directly impact fertilization rate, early embryonic development, and reproductive outcome in mammals. Abstract : Several kinases, signal molecules, and factors are involved in oocyte journey from M‐I to M‐II stage and PB‐I extrusion to convert oocyte in a female gamete in mammals. The ORC‐4 surrounds the chromosome required to be extruded in PB‐I. Both Rho family GTPase and Cdc‐42 are instrumental in the formation and extrusion of PB‐I. Oocyte journey from M‐I to M‐II stage is very important in order to release PB‐I that enable oocytes to get converted into right female gamete required for fertilization and early embryonic development in several mammalian species including human.